Effect of TiO2-coated substrate photocatalysis on chlopyrifos insecticide degradation - Whangchai K. (2017)
© 2016, Int. J. of GEOMATE. All rights reserved. The efficiencies of photocatalysis using TiO 2 -coated substrates to reduce chlorpyrifos insecticides was evaluated. Three different glass substrates (glass ball, glass slide and glass bead) were prepared and tested with KI solution for efficiency of oxidation test. It was found that TiO 2 -coated glass beads at 45 mg/ml for 60 min had the highest iodine liberation rate. A 1 mgL -1 standard chlorpyrifos was subjected to those TiO 2 -coated substrates photocatalysis for 15, 30, 45 and 60 minutes. The percentage reduction of chlorpyrifos was calculated. It was shown that TiO 2 -coated glass bead photocatalysis had high reduction rate of chlorpyrifos concentration within 15 minutes, which correlated with an increase in iodine liberation rate. The effectiveness of TiO 2 in photocatalysis to reduce contaminated chlorpyrifos in Chinese kale was determined by treatments with different TiO 2 -coated substrate photocatalysis and sampled every 15 minutes for 60 minutes. It was found that TiO 2 -coated glass bead reduced chlorpyrifos concentration to 53% when compared with the control. In addition, in the quality of Chinese kale after treatment withTiO 2 in photocatalysis and stored for 12 days at 5 °C was also investigated. There was no significant difference in the quality of Chinese kale in weight loss, leaf color, total soluble solids and ascorbic acid content.